Urban and Architectural Impacts of Religious Visits on the Architecture of Holy Shrines: The Case of Al Attaba Al Alaweya (Journal of University of Babylon for Engineering Sciences, 2018)
The religious visit to the holy shrines is an important aspect of the life and behavior of Muslims because of the connection to a religious and spiritual conviction based on frequent statements sayings by the great Prophet Muhammad and his holy family, that the imam intended to visit is present is hearing and responding the greeting. The visit has its impact on the heart from the spiritual point of view, in addition to the request for intercession because they are close to Allah. The visit to any imam is a visit to the Prophet, also as if he visited the throne of God. The importance of the visit and then the number of visitors from an architectural and planning point of view form important criterion in the development and change of the architecture of the threshold and the urban adjacent fabric because its include the behavioral, social and cultural functional dimensions, as well as the decrees and traditions of the visit during religious events. The absence of a clear knowledge of the architectural and urban influences of religious visits in the building of the holy shrines, The aim of this paper is to study and analyze the impact of the concept of the visit and the number of visitors in the development of the architecture of the threshold and surrounding urban fabric. It also deals with the ability of accommodating the urban spaces of the increasing numbers of visitors and their religious, social and cultural activities and the need to study them as a functional criterion in the development of the architecture of the thresholds in general and the Imam Ali threshold and sacred subject matter in particular